PENGARUH PEMBELAJARAN BERBASIS PERMAINAN (GAME BASED LEARNING) MATERI SISTEM TATA SURYA TERHADAP HASIL BELAJAR SISWA KELAS VI SEKOLAH DASAR - Rafli Akbar Putra; Julianto; Erita Indah Cumalasari; Rizka Lucky Fusianita; Fitria Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The teacher’s misalignment in applying learning techniques or models has led to student learning outcomes in the Solar System material falling short of the Minimum Completeness Criteria (KKM). To address this, efforts are needed, one of which involves using Game-Based Learning assisted by Kahoot! digital media. This study aims to assess the impact of Game-Based Learning, supported by Kahoot!, on improving student learning outcomes in the IPAS subject. The research follows the Classroom Action Research model proposed by Kemmis and McTaggart, consisting of two cycles. The study was conducted in a sixth-grade class at Petemon State Elementary School, comprising 27 students. The results indicated that the average student learning outcomes increased from 75 in cycle 1 to 88 after cycle 2. In conclusion, Game-Based Learning with Kahoot! digital media effectively enhanced students’ understanding of the Solar System.